Postmortem morphometry of the thyroid gland in Bangladeshi people - Razzaque, Iftekhar Bin; Begum, Rezia; Mustafa, Rashed; Benzir, Maskura (Bangladesh Medical Journal Khulna, 2025)
Background: Estimation of the size of the thyroid gland is clinically important in the evaluation and management of thyroid disorders, particularly in cases, where medical treatment is not sufficient to manage thyroid disorders, specially in malignancy and when there are compressive symptoms. The understanding of the anatomical relations, functional states and blood supply of the thyroid gland is of paramount importance to thyroid surgeons. Objectives: The present study aimed to determine the morphometric values of the thyroid gland in different age groups and both sexes in Bangladeshi people. Methodology: This cross sectional descriptive study was conducted in department of Anatomy, Rajshahi Medical College from December, 2017 to December, 2018. The study was performed on 60 cadaveric thyroid gland, collected from unclaimed dead bodies in department of Forensic Medicine and Toxicology. The samples were categorized in three groups according to age. Morphometry of the thyroid glands was done to measure length, breadth and thickness of both lobes and isthmus. Weight and volume of the whole gland were also measured. Results: The mean length, breadth and thickness of the right and left lobe of the thyroid gland were 3.39 ± + 0.55 cm and 3.31 ± 0.51 cm, 2.48 ± 0.53 cm and 2.41 ± 0.52 cm, 1.61 ± 0.27 cm and 1.56 ± 0.31 cm respectively. The isthmus was absent in 10 out of 60 cadavers (16.7%). Pyramidal lobe was found in 23 cadavers (38.3%), arising most commonly from left side of the isthmus. The mean weight and volume were 18.16 ± 2.73 gm and 14.37 ± 2.52 ml respectively. The length of lobes, weight and volume of the gland were found higher in males than females. Conclusion: The morphological parameters of the thyroid gland, also its weight and volume, vary significantly with the ages and sexes of the individuals. Bang Med J Khulna 2023; 56; 14-18